Arcillas caoliníticas del departamento del cauca (1988)
The present study contains the results of mineralogical analysis made by X-ray diffraction of a set of samples of sedimentary fluvial-lacoustre clays and others wichare produced by weathering of ignimbrites and tonalitic rocks. The mineralogical analysis was practiced over clay fraction (particles with 2 microns in grain diameter). Tecnological test was made too, in order to establish the mineralogical composition effect over quality of bricks made in around Popayan. Tecnological test was made too, in order to establish the mineralogical composition effect over quality of bricks made in around Popayán. The principal mineral identified in all samples was kaolinite in different degrees of structural order.